Exercise Modification of Directional Hand Movement to Improve The Punch Speed in Pencak Silat - Haqiyah, Aridhotul; Adara, Reza Anggriyashati; Riyadi, Dani Nur; Lubis, Johansyah; Widiastuti, Widiastuti (Journal of Physical Education Health and Sport, 2020)
In performing pencak silat, speed is needed. This study aims to determine the effect of modification exercises directional hand movement on the punch speed in pencak silat. The method used was an experiment with a one group pre-test and post-test design. The sample in this study was 32 students (20.15+0.84) at the Universitas Islam 45 Bekasi. Based on the results of the analysis, it can be concluded that the exercise modification of directional hand movement improve the punch speed in pencak silat. The t value = 8,258, with df = 31, and the p-value = 0.000 <0.05. Thus it can be concluded that there is an increase in the speed of the punches through the modification of the exercise directional hand movement. This can be an input for coaches and sports teachers as a reference for variations in exercise in increasing the physical component of speed in martial arts.